Catalytic degradation of Acid Orange 7 by H2O2 as promoted by either bare or V-loaded titania under UV light, in dark conditions, and after incubating the catalysts in ascorbic acid. (2nd October 2015) - Piumetti, Marco; Freyria, Francesca S.; Armandi, Marco; Saracco, Guido; Garrone, Edoardo; Gonzalez, Giovanny Esteban; Bonelli, Barbara
Abstract: Pure and V-loaded mesoporous titania (with 2.5 wt-% V) were prepared by template-assisted synthesis and compared to commercial titania (Degussa P25), both as such and after vanadium loading. Mesoporous TiO2 occurred as pure anatase nanoparticles with higher surface area (SSA = 150 m 2  g −1 ) than P25 (SSA = 56 m 2  g −1 ). Degradation of the azo dye Acid Orange 7 by H2 O2 was used as a test reaction: under UV light, no difference emerged between mesoporous TiO2 and P25, whereas in dark conditions, higher SSA of the mesoporous sample resulted in higher conversions. Under UV illumination, surface V 5+ species inhibited photocatalytic activity, by forming inactive V 4+ species. Similarly, in dark conditions, V 5+ surface species reacted with H2 O2, likely yielding ·O2 H radicals and reducing to V 4+ . On the contrary, V-containing catalysts were very active after pretreatment with ascorbic acid, which reduced V 5+ species to V 3+ species, the latter promoting very lively a Fenton-like reaction. Abstract :